A rare case of cutaneous leishmaniasis in Kathmandu presenting with features of bacterial skin infection: A case report. Issue 3 (11th March 2023) - Regmi, Anil; Adhikari, Biplov; Karki, Pragya; Baral, Suwash; Adhikari, Irusha Rani
Abstract: Leishmaniasis is an infectious disease caused by different species of genus Leishmania and transmitted by sandflies. Lesions of CL are most commonly present in the exposed areas, and the most familiar morphological type is papulo‐nodular. The diagnosis of CL should be considered while dealing with common skin lesions, as well as encountering uncommon pathologies. We present a case of a 26‐year‐old man living in Kathmandu originally from Humla whose clinical course was complicated by unsuccessful treatment with suspicion of bacterial skin infection. The patient first presented with an erythematous papule with some scale and crust with central ulceration over the left side of his upper lip and mild fever. With the suspicion of bacterial infection, he was initially treated with antibiotics, which showed no improvement prompting the referral to a tertiary center with further diagnostic workup. Punch biopsy confirmed the presence of amastigote form of leishmaniasis Donovan bodies. Also, the rk39 antibody test was positive. Clinicians need to pay more effort to the diagnosis of CL and include it in the differential diagnoses of patients presenting with typical lesions even if the region is not known to be endemic for CL or in the patient with no known history of insect bite. Abstract : Clinicians need to pay more effort to the diagnosis of CL and include it in the differential diagnoses of patients presenting with typical lesions even if the region is not known to be endemic for CL or in the patient with no history of insect bites.